Development of Visits on the Main Tourism Object in West Sumatera - Mariya, Sri; Rahmanelli, Rahmanelli; Novio, Rery; Suasti, Yurni; Ahyuni, Ahyuni (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
The number of visits has an important in the development of tourism objects. This research purposed to know the development of the main tourist objects in West Sumatera based on the number of visits using the theory by Buttler 1980 with the Tourism Area Life Cycle (TALC) model.The methode of this research is descriptive. The sample is the main tourist attraction in West Sumatera based on the number of local tourist visits. The type of data analysis used secondary data analysis through TALC models with exploration, involvement, development, consolidation, stagnation, decline levels, and the rejuvenate stage. Data sources used are secondary data from the Central Statistics Agency (BPS).The results of this research in five-years (2012-2016), the development of the number of visits to the main tourism objects in West Sumatera: a) Bukittinggi City and Padang City are at the development stage, b) Padang Panjang City and Sawahlunto City at the decline stage, c) Pariaman city at the stage of stagnation, and d) Payakumbuh City and Solok City at the rejuvenate stage